Public participation in urban design with augmented reality technology based on indicator evaluation - Wang, Yuchen; Lin, Yin-Shan (Frontiers in Virtual Reality, 2023)
Decision-making processes in traditional urban design approaches are mainly top-down. Such processes have defects including not only taking a long time to examine the design results, but also leading to irreversible impacts after design implementation. Policy-makers and researchers stress the importance of collaborating with different stakeholders in the process of urban design policies or guidelines making in order to minimize these negative impacts. However, introducing public participation in an urban design from the bottom up is challenging, especially when the process involves abstract urban design concepts such as the indicators. This paper explores a new workflow aimed at enhancing public participations to cooperate in urban design work with the help of a newly designed platform tool powered by mobile augmented reality technologies. The platform is intuitive to use and displays scenes of potential urban design results by superimposing the virtual models on the real-world environment on mobile devices. The public stakeholders are provided with this platform on site to evaluate the initial values of urban design indicators by interacting with the prototype design along with immersive experience. They can also get familiar with the concepts of the given indicators during this process, which helps them better understand the implications of guidelines in future published urban design drafts and estimate the potential results. Their feedback is collected, which can help urban designers further optimize the indicators in urban design guidelines making in order to improve their rationality. This process of urban design involving public participation is repeatable, which makes it possible to continuously adjust the design results. A user study has been conducted to examine the platform’s usability and its ability to enhance the public familiarity with the concepts of given indicators and their willingness to participate in urban design evaluation. The study also attests to the possibility of a workflow that integrates public feedback with the urban design process.